CSIG-44. TREATMENT WITH THE CASEIN KINASE 2 INHIBITOR, CX-4945, SENSITIZES MEDULLOBLASTOMA TO TEMOZOLOMIDE. (5th November 2018) - Nitta, Ryan; Li, Gordon
Abstract: Medulloblastoma (MB) is the most common malignant pediatric brain tumor, accounting for 20% of all cases. While current treatments result in a cure rate of 70–75%, the surviving patients are afflicted with neurocognitive impairment, endocrine dysfunction, and a severe decrease in quality of life. Consequently, better and more effective treatments are needed to treat these young patients. Casein kinase 2 (CK2) is an intriguing therapeutic target because MB patients with elevated levels of CK2 expression have a significantly worse prognosis. To elucidate the role of CK2 in MB, we modulated CK2 expression in multiple MB cell lines (Daoy and Med1-MB). We discovered that exogenous expression of either CK2 isoform, CK2a or CK2b, increased MB cell growth and significantly decreased survival in mice that were injected intracranially with the modulated cell lines. Consistently, we demonstrated that knocking down CK2 expression using CRISPR-Cas9 or inhibiting CK2 activity using the CK2 inhibitor, CX-4945, decreased MB growth. We conducted a high throughput to identify new compounds that could work synergistically with CX-4945. We screened over 4, 000 FDA approved compounds and determined that temozolomide (TMZ) enhanced the efficacy of CX-4945. We corroborated these findings when we verified that knocking out CK2a or CK2b sensitized Daoy cells to TMZ treatment. Interestingly we also determined that combinatorial treatment of CX-4945 and TMZ enhanced MB apoptosis and decreased cell growth. To elucidate the mechanism by which CK2 inhibition sensitized MB cells to TMZ we analyzed the expression of b-catenin, a known regulator of O-6-methylguanine-DNA methyltransferase (MGMT) activity. We determined that inhibition or loss of CK2 activity reduced b-catenin expression, which in turn lead to a decrease in MGMT expression. Together, our findings suggest that CK2 is a novel therapeutic target for MB and that combining CX-4945 and TMZ can lead to a promising new MB therapy.